Increasing colon cancer testing in rural Colorado: evaluation of the exposure to a community-based awareness campaign - Norman Ned; Dickinson Miriam; Emsermann Caroline; Zittleman Linda; Winkelman Kathy; Linn Grace; Westfall John M (BMC, 2009)
Abstract Background Despite effective prevention and early detection screening methods, colorectal cancer is the second leading cause of cancer death in the United States. Colorectal cancer screening community-based interventions are rare, and the literature lacks information about community-based intervention processes. Using participatory research methods, the High Plains Research Network developed a community-based awareness and educational intervention to increase colorectal cancer screening rates in rural northeastern Colorado. This study describes the program components and implementation and explores whether the target population was exposed to the intervention, the reach of the individual intervention components, and the effect on screening intentions. Methods A random digit dial survey was conducted of residents age 40 and older in the first 3 communities to receive the intervention to estimate exposure to the intervention and its effect on colorectal cancer screening intentions. Results Exposure to at least intervention component was reported by 68% of respondents (n = 460). As the level of exposure increased, intentions to talk to a doctor about colorectal cancer screening increased significantly more in respondents who had not been tested in the past 5 years than those who had (p = .025). Intentions to get tested increased significantly in both groups at the same rate as level of exposure increased (p < .001). Conclusion Using local community members led to the successful implementation of the intervention. Program materials and messages reached a high percentage of the target population and increased colorectal cancer screening intentions.